Assessment of three human FcεRI-transfected RBL cell-lines for identifying IgE induced degranulation utilizing peanut-allergic patient sera and peanut protein extract - Ladics, G.S.; van Bilsen, J.H.M.; Brouwer, H.M.H.; Vogel, L.; Vieths, S.; Knippels, L.M.J. (Regulatory toxicology and pharmacology, 2008)
Specific IgE sera screening studies are employed to investigate protein cross-reactivity. Such nonfunctional immunochemical methods cannot measure the biological activity of proteins. Therefore, an assay using RBL cells transfected with human FcεRI was developed. Our objective was to evaluate the degranulation of three cell-lines expressing either the α-(RBL-hEI a-2B12 and RBL-30/25 cells) or α-, β-, and γ-subunits (RBL SX-38) of the human FcεRI by β-hexosaminidase release. Purified human IgE and serum-derived polyclonal IgE from peanut-allergic subjects following challenge with anti-IgE or peanut protein extract, respectively, were utilized. Robust degranulation was induced in all three: RBL-30/25 (84%), -hEI a-2B12 (54%), SX-38 (94%), respectively, using purified IgE + anti-human IgE. Good release (18%, 40–45%, and 65%, respectively) occurred for one peanut-allergic subject + peanut extract with all cell-lines. With serum from three other peanut-allergic subjects, no β-hexosaminidase release occurred with RBL-hEI a-2B12 cells + peanut extract, while only serum from one subject induced good degranulation, 30% and 60%, respectively, with RBL-30/25 and RBL SX 38 cells. Consistent degranulation with a potent food allergen (peanuts) was not observed. The assay’s utility in safety assessment, predictive value and reproducibility for evaluating the cross-reactivity of proteins with allergens needs further investigation with additional proteins and well-characterized sera.